The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pathogens9070540
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Puumala orthohantavirus Strains in the Pre-Kama Area of the Republic of Tatarstan, Russia

Abstract: Puumala orthohantavirus (PUUV) causes nephropathia epidemica (NE), a mild form of hemorrhagic fever with renal syndrome (HFRS) commonly diagnosed in Europe. The majority of HFRS cases in the European part of Russia are diagnosed in the Volga Federal District, which includes the Republic of Tatarstan (RT). The current study aims to analyze the genetic variability of PUUV in Pre-Kama region of the RT bounded by the Volga, Kama, and Vyatka rivers. In 2017, bank voles were caught in seven isolated forest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Similar to what has been observed in other research, we observed 100% amino acid identity of the PUUV S-segment fragments to the LAT lineage within our trapping sites [ 33 ]. Despite other PUUV lineages, we observed no distinct molecular signatures within our S-segments, suggesting that the Ukrainian sequences are not a new lineage.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to what has been observed in other research, we observed 100% amino acid identity of the PUUV S-segment fragments to the LAT lineage within our trapping sites [ 33 ]. Despite other PUUV lineages, we observed no distinct molecular signatures within our S-segments, suggesting that the Ukrainian sequences are not a new lineage.…”
Section: Discussionsupporting
confidence: 91%
“…The intergroup sequence divergence was up to 6.0% ( Figure 2 , Supplementary Table S2 ). Analysis of these sequences and those previously published by Davidyuk et al [ 19 ], as well as other PUUV sequences belonging to the RUS lineage (Samara_49/CG/2005, Puu/Kazan, CG1820, DTK/Ufa-97 strains), showed 2.6–6.9% divergence ( Figure 3 , Supplementary Table S3 ). Throughout this article, we will use the terms ‘Pre-Kama sequences’/or ‘Pre-Kama strains’, referring to previously identified strains in the Pre-Kama area.…”
Section: Resultsmentioning
confidence: 52%
“…RT-PCR amplification was carried out using TaqPol polymerase (Evrogen, Moscow, Russia) as specified by the manufacturer. Forward and reverse primers used both for RT-PCRs amplification and sequencing were designed as described by Davidyuk et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…N protein is the most abundant viral protein synthesized early after infection [41]. This protein plays a role in intracellular transportation and assembly of mature virions [3,42].…”
Section: Genome Structure Of Orthohantavirusesmentioning
confidence: 99%